Factorial validity and invariance of the Muet writing rating scale: empirical and theoretical correspondence - Abu Kassim, Noor Lide; Nordin, Mohamad Sahari (2010)
The validity of performance assessment depends to a large extent on the rating scale that is used in the assessment procedure. It delineates the theoretical construct being measured and yield considerable influence on how performances are judged and interpreted. Implications of the use of rating scales are therefore far too important to be taken lightly, particularly in high-stakes standardized tests. This study investigates the factorial validity and invariance of a writing rating scale used in such a test – the Malaysian University English Test – in terms of its correspondence to empirical data and the theoretical construct of ESL writing through the use of confirmatory factor analysis (CFA). To test for factorial validity, a measurement model was developed based on the construct definition of the MUET rating scale and tested using AMOS, a data-fitting programme.